2010
DOI: 10.1002/hbm.20937
|View full text |Cite
|
Sign up to set email alerts
|

Independent component analysis of erroneous and correct responses suggests online response control

Abstract: After errors in reaction tasks, a sharp negative wave emerges in the event-related potential (ERP), the error (related) negativity (Ne or ERN). However, also after correct trials, an Ne-like wave is seen, called CRN or Nc, which is much smaller than the Ne. This study tested the hypothesis whether Ne and Nc reflect the same functional process, and whether this process is linked to online response control. For this purpose, independent component analysis (ICA) was utilized with the EEG data of two types of reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 45 publications
3
55
3
Order By: Relevance
“…In line with previous findings Falkenstein, 2004;Johannes et al, 2002;Kaczkurkin, 2013;Pailing & Segalowitz, 2004a;Schreiber et al, 2012) we found that the magnitude of ERN decreased with increasing task difficulty. Effects of task difficulty on CRN amplitude have been observed less consistently across studies with some reporting increased CRN with higher difficulty (Kaczkurkin, 2013;Pailing & Segalowitz, 2004b;Schreiber et al, 2012) and some reporting no effects (Falkenstein, 2004;Hoffmann & Falkenstein, 2010). The present study did not reveal effects of difficulty on the CRN.…”
Section: Error Reaction Time (Ms)contrasting
confidence: 67%
See 4 more Smart Citations
“…In line with previous findings Falkenstein, 2004;Johannes et al, 2002;Kaczkurkin, 2013;Pailing & Segalowitz, 2004a;Schreiber et al, 2012) we found that the magnitude of ERN decreased with increasing task difficulty. Effects of task difficulty on CRN amplitude have been observed less consistently across studies with some reporting increased CRN with higher difficulty (Kaczkurkin, 2013;Pailing & Segalowitz, 2004b;Schreiber et al, 2012) and some reporting no effects (Falkenstein, 2004;Hoffmann & Falkenstein, 2010). The present study did not reveal effects of difficulty on the CRN.…”
Section: Error Reaction Time (Ms)contrasting
confidence: 67%
“…These findings indicate that group differences might not be obtained in tasks that are very difficult (Kaczkurkin, 2013), do not include response conflict, have a undetermined stimulus-response mapping or require learning . Together with results indicating that the ERN varies significantly across tasks (Hoffmann & Falkenstein, 2010;Riesel, Weinberg, Endrass, Meyer, & Hajcak, 2013;Segalowitz et al, 2010) this emphasizes the impact of varying task characteristics on electrophysiological markers of performance monitoring and highlights the need to examine a wide range of task and systematically explore the influence of task characteristics.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations